2009
DOI: 10.1007/s11262-009-0425-3
|View full text |Cite
|
Sign up to set email alerts
|

Natural insertions within the N-terminal region of the coat protein of Maize dwarf mosaic potyvirus (MDMV) have an effect on the RNA stability

Abstract: A 13 amino acid residue insertion was found in the N-terminal region of the coat protein of several Maize dwarf mosaic virus isolates (MDMV). These insertions seem to be the result of a direct duplication event, but differ in some positions. In order to evaluate the influence of the insertion on the RNA secondary structure and stability, the RNA secondary structures and minimum free energies (MFE) of all existing MDMV coat protein sequences were estimated using three different softwares, the Vienna RNA Package… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Comparative computer-based analysis revealed that in some isolates the insertion exhibited a high degree of conservation both in terms of nucleic acid base sequence and localization. Further analysis suggested that the insertion plays a role in virus RNA stability [39].…”
Section: Recombination Analysismentioning
confidence: 99%
“…Comparative computer-based analysis revealed that in some isolates the insertion exhibited a high degree of conservation both in terms of nucleic acid base sequence and localization. Further analysis suggested that the insertion plays a role in virus RNA stability [39].…”
Section: Recombination Analysismentioning
confidence: 99%
“…JQ280313.1), MDMV-Sz0605 (GenBank accession no. FM883211.2 [49], MDMV-Mv0801 (GenBank accession no. FM883164.2 [49] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…FM883211.2 [49], MDMV-Mv0801 (GenBank accession no. FM883164.2 [49] (Table 1). RACE was also performed for MDMV-Italy (GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
“…This protein subunit of MDMV has a molecular weight of 28.5 × 10 3 according to amino acid analyses [ 32 ]. The C-terminal regions of the coat protein primarily plays a role in the process of encapsidation and cell-to-cell transport and the flexible N-terminus is involved in long distance and systemic transport and contains the DAG motif essential for aphid transmission competence [ 33 ].…”
Section: Genomementioning
confidence: 99%